A method for preparing high-efficiency inorganic perovskite solar cells by surface passivation
By spin-coating a mixed solution of FAI and MAI onto the surface of a perovskite thin film to form a heterojunction layer, the problem of low efficiency in all-inorganic perovskite solar cells was solved, achieving a high-efficiency photoelectric conversion effect.
Patent Information
- Application Number
- CN202211632158.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-12-19
AI Technical Summary
The photoelectric conversion efficiency of all-inorganic perovskite solar cells is relatively low, mainly due to the wide band gap of inorganic perovskite and severe non-radiative recombination on the surface, resulting in a large open-circuit voltage loss.
A passivation film is spin-coated onto the surface of a perovskite thin film, and a heterojunction layer is formed by a mixed solution of FAI and MAI to improve surface defects, suppress charge recombination, and promote charge transfer.
This improved the light absorption efficiency of perovskite thin films, optimized energy level positions, promoted carrier transport, enhanced current performance, and ultimately achieved high photoelectric conversion efficiency.
Smart Images

Figure CN115835658B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite solar cell technology, specifically relating to a method for preparing high-efficiency inorganic perovskite solar cells by surface passivation. Background Technology
[0002] In the past decade or so, perovskite solar cells have attracted widespread attention due to their low manufacturing cost, solution-based fabrication, and high photoelectric conversion efficiency. The high absorption coefficient of perovskite allows ultrathin films of approximately 500 nm to absorb the entire solar spectrum. This combination of characteristics makes it possible to create low-cost, high-efficiency, thin, lightweight, and flexible solar modules. Hybrid organic-inorganic lead or tin halide materials are most commonly used as perovskite materials for the light-harvesting active layer, such as methylamine lead halide and all-inorganic cesium lead halide, which are inexpensive and easy to manufacture. The efficiency of solar cells using these materials increased from 3.8% in 2009 to 25.5% in 2020. However, organic-component perovskite solar cells are relatively sensitive to heat and prone to decomposition, resulting in poor device stability. All-inorganic CsPbI₂... 1.5 Br 1.5 The material has attracted widespread attention from researchers due to its excellent stability under high temperature, high humidity and ultraviolet light conditions.
[0003] However, currently, the photoelectric conversion efficiency of all-inorganic perovskite solar cells is still significantly lower than that of organic-inorganic hybrid perovskite solar cells. This is partly due to the wider band gap of inorganic perovskites (CsPbI). 1.5 Br 1.5 One issue is that the bandgap of perovskite films is approximately 2.10 eV. Secondly, photovoltaic devices based on all-inorganic perovskite materials suffer from severe non-radiative recombination on the surface, leading to significant open-circuit voltage (Voc) losses and consequently, generally low photoelectric conversion efficiency. Therefore, improving the surface states of perovskite thin films is crucial. Summary of the Invention
[0004] To address the problems in the prior art, this invention provides a method for preparing high-efficiency inorganic perovskite solar cells by surface passivation, which solves the defects of the prior art. By spin-coating a passivation film onto the perovskite film, the surface defects of the perovskite film are effectively improved, charge recombination is suppressed, and charge transfer is promoted.
[0005] To achieve the above technical objectives, the technical solution of the present invention is as follows:
[0006] A method for preparing high-efficiency inorganic perovskite solar cells by surface passivation, comprising:
[0007] Step 1: Select a glass substrate with an ITO electrode cathode;
[0008] Step 2: Prepare a SnO2 electron transport layer on the surface of the ITO electrode anode to obtain an ITO / SnO2 substrate;
[0009] Step 3: A mixed solution of CsI and PbBr2 is obtained by a one-step method, and CsPbI is prepared on the SnO2 electron transport layer. 1.5 Br 1.5 Perovskite films were obtained, yielding ITO / SnO2 / CsPbI 1.5 Br 1.5 Base;
[0010] Step 4, in CsPbI 1.5 Br 1.5 Spin-coating a mixed solution of FAI and MAI onto a perovskite thin film to prepare a FAI+MAI passivation layer, yielding an ITO / SnO2 / CsPbI layer. 1.5 Br 1.5 / FAI+MAI substrate;
[0011] Step 5: Spin-coating Spiro-OMeTAD solution onto the surface of the FAI+MAI passivation layer to prepare a hole transport layer, resulting in ITO / SnO2 / CsPbI 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD substrate;
[0012] Step 6: Deposit an anodic buffer layer—molybdenum oxide—on the surface of the hole transport layer to obtain...
[0013] ITO / SnO2 / CsPbI 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD / Molybdenum oxide substrate;
[0014] Step 7: Deposit a metallic silver electrode on the anode buffer layer-molybdenum oxide to prepare an all-inorganic perovskite solar cell with surface passivation.
[0015] The thickness of the glass substrate with the ITO electrode cathode in step 1 is 0.7-1 mm, and the thickness of the ITO electrode cathode is 50-100 nm.
[0016] Before use, the glass substrate with the ITO electrode cathode in step 1 is ultrasonically cleaned in conductive glass cleaning solution, deionized water, acetone and isopropanol for 20 minutes in sequence.
[0017] Furthermore, the cleaned glass substrate with the ITO electrode cathode is treated in a UV-Ozone for 15-30 minutes.
[0018] The electron transport layer fabrication of the ITO / SnO2 substrate in step 2 includes:
[0019] 50 μL of SnO2 solution was spin-coated in air at 4000 rpm for 30 s onto a glass substrate with an ITO electrode anode that had been treated with UV-Ozone.
[0020] A glass substrate with an ITO electrode anode and SnO2 spin-coated was placed on a heating stage and annealed at 150°C in air for 30 min to prepare a SnO2 electron transport layer with a thickness of 10 nm to 60 nm, thus obtaining an ITO / SnO2 substrate.
[0021] The ITO / SnO2 / CsPbI in step 3 1.5 Br 1.5 The preparation of the substrate includes:
[0022] Dissolve 367 mg of PbBr2, 260 mg of CsI, and 138.4 mg of DMAI in 1.15 mL of DMSO and stir at 100 °C until completely dissolved to obtain CsPbI. 1.5 Br 1.5 Solution;
[0023] The ITO / SnO2 substrate was placed in a glove box under N2 environment, and 40-45 μL of 1M CsPbI was added. 1.5 Br 1.5 The solution was spin-coated onto the ITO / SnO2 substrate at rotation speeds of 1000 rpm for 5 s and 2500 rpm for 50 s.
[0024] Spin-coated with CsPbI 1.5 Br 1.5 The solution-containing ITO / SnO2 substrate was annealed on a hot plate at 170℃ for 8-10 min to prepare CsPbI with a thickness of 200-600 nm. 1.5 Br 1.5 The thin film, namely the ITO / SnO2 / CsPbI film, is obtained. 1.5 Br 1.5 Base.
[0025] The preparation of the FAI+MAI passivation layer in step 4 includes:
[0026] Take 8 mg of FAI and 0.5 mg of MAI solid and dissolve them in 1 mL of isopropanol. Stir at room temperature until completely dissolved to obtain a mixed solution of FAI and MAI.
[0027] Will ITO / SnO2 / CsPbI 1.5 Br 1.5 The substrate was placed in a nitrogen atmosphere in a glove box, and 30 μL of the mixed solution was incubated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere.1.5 Br 1.5 Spin-coat the substrate for 30 seconds;
[0028] Spin-coating ITO / SnO2 / CsPbI with a mixed solution 1.5 Br 1.5 The substrate is annealed on a 100℃ hot plate for 8-10 min to prepare a FAI+MAI passivation layer with a thickness of 10-60 nm, thus obtaining...
[0029] ITO / SnO2 / CsPbI 1.5 Br 1.5 / FAI+MAI substrate.
[0030] The preparation of the hole transport layer in step 5 includes:
[0031] Dissolve 72.3 mg of Spiro-OMeTAD in 1 mL of chlorobenzene and stir at room temperature until completely dissolved to obtain a Spiro-OMeTAD solution.
[0032] Will ITO / SnO2 / CsPbI 1.5 Br 1.5 The FAI+MAI substrate was placed in a glove box under a nitrogen atmosphere, and 30 μL Spiro-OMeTAD was rotated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere. 1.5 Br 1.5 A hole transport layer was prepared by spin-coating on a FAI+MAI substrate for 30 seconds, resulting in ITO / SnO2 / CsPbI. 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD substrate.
[0033] The preparation of the anode buffer layer in step 6 includes:
[0034] Under nitrogen atmosphere, a molybdenum oxide anolyte buffer layer was deposited on the Spiro-OMeTAD hole transport layer using thermal evaporation to obtain a layer with a thickness of 9-11 nm and an area of 2 cm². 2 The molybdenum oxide anolyte buffer layer, i.e., ITO / SnO2 / CsPbI, is obtained. 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD / Molybdenum oxide substrate.
[0035] The preparation of the silver electrode in step 7 includes:
[0036] At room temperature, a metallic silver electrode was deposited on the molybdenum oxide anode buffer layer using a thermal evaporation method, resulting in a electrode with a thickness of 80 nm and an area of 0.04 cm². 2The metallic silver electrode is used to complete the fabrication of perovskite solar cells.
[0037] As can be seen from the above description, the present invention has the following advantages:
[0038] This invention addresses the shortcomings of existing technologies by spin-coating a passivation film onto a perovskite film, effectively improving surface defects in the perovskite film, suppressing charge recombination, and promoting charge transfer.
[0039] FAI can be spin-coated onto the perovskite surface to form FA-CsPbI. 1.5 Br 1.5 The heterojunction layer fills grain boundaries and defects on the perovskite surface, suppressing nonradiative recombination. When FAI and MAI are used in combination, MA effectively promotes the crystallinity of the heterojunction layer, thereby further improving the film quality. The resulting narrower bandgap heterojunction layer reduces optical losses in the perovskite film, improves light absorption, and enhances current performance. Simultaneously, the heterojunction layer optimizes the energy level positions of the perovskite cell, thereby promoting carrier transport and ultimately achieving a highly efficient CsPbI1.5Br1.5 perovskite solar cell. Attached Figure Description
[0040] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell that promotes the growth of all-inorganic perovskite thin film crystals according to Embodiment 1 of the present invention.
[0041] Figure 2 This is the IV characteristic curve of a perovskite solar cell that promotes the growth of all-inorganic perovskite thin film crystals according to a specific embodiment 1 of the present invention.
[0042] Figure 3 This is a schematic diagram of the fabrication process of a perovskite solar cell that promotes the growth of all-inorganic perovskite thin film crystals, according to a specific embodiment 1 of the present invention.
[0043] Figure reference numerals: 1. Glass substrate with ITO cathode electrode; 2. SnO2 electron transport layer; 3. CsPbI 1.5 Br 1.5 4. Perovskite thin film, 5. Passivation layer, 6. Hole transport layer, 7. Molybdenum oxide anode buffer layer, 8. Metallic silver electrode. Detailed Implementation
[0044] Combination Figures 1 to 3 This article describes a specific embodiment of the present invention in detail, but does not limit the scope of the claims of the present invention in any way.
[0045] Example 1
[0046] like Figure 1 and Figure 3As shown, a method for preparing high-efficiency inorganic perovskite solar cells by surface passivation includes:
[0047] Step 1: Clean the ITO / glass substrate 1 sequentially with conductive glass cleaning solution, deionized water, acetone and isopropanol for 20 minutes each, and set aside for later use. The sheet resistance of the ITO layer is 7 ohms. After cleaning, place it in UV-Ozone for 15 minutes. The thickness of the glass substrate with the ITO electrode cathode is 0.7 mm, and the thickness of the ITO electrode cathode is 50 nm.
[0048] Step 2: Place the glass substrate with SnO2 spin-coated and ITO electrode anode on a heating stage and anneal it at 150°C in air for 30 min to prepare a SnO2 electron transport layer with a thickness of 10 nm and obtain an ITO / SnO2 substrate.
[0049] Step 3: Dissolve 367 mg of PbBr2, 260 mg of CsI, and 138.4 mg of DMAI in 1.15 mL of DMSO, and stir at 100 °C until completely dissolved to obtain CsPbI. 1.5 Br 1.5 Solution; The ITO / SnO2 substrate was placed in a glove box under N2 environment, and 40 μL of 1M CsPbI solution was added. 1.5 Br 1.5 The solution was spin-coated onto the ITO / SnO2 substrate at 1000 rpm for 5 s and 2500 rpm for 50 s, and then allowed to stand for 20 min. The CsPbI solution was then spin-coated onto the substrate. 1.5 Br 1.5 The solution-containing ITO / SnO2 substrate was annealed on a hot plate at 170℃ for 8 min to prepare a CsPbI layer with a thickness of 200 nm. 1.5 Br 1.5 The thin film, namely the ITO / SnO2 / CsPbI film, is obtained. 1.5 Br 1.5 Base;
[0050] Step 4: Dissolve 8 mg of FAI and 0.5 mg of MAI solid in 1 mL of isopropanol, and stir at room temperature until completely dissolved to obtain a mixed solution of FAI + MAI; Add ITO / SnO2 / CsPbI 1.5 Br 1.5 The substrate was placed in a nitrogen atmosphere in a glove box, and 30 μL of the mixed solution was incubated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere. 1.5 Br 1.5 Spin-coating was performed on the substrate for 30 seconds; the ITO / SnO2 / CsPbI solution was then spin-coated. 1.5 Br 1.5The substrate was annealed on a hot plate at 100°C for 8 minutes to prepare a 10 nm thick FAI+MAI passivation layer, thus obtaining the ITO / SnO2 / CsPbI layer. 1.5 Br 1.5 / FAI+MAI substrate;
[0051] Step 5: Dissolve 72.3 mg of Spiro-OMeTAD in 1 mL of chlorobenzene and stir at room temperature until completely dissolved to obtain a Spiro-OMeTAD solution; Add ITO / SnO2 / CsPbI 1.5 Br 1.5 The FAI+MAI substrate was placed in a glove box under a nitrogen atmosphere, and 30 μL of Spiro-OMeTAD was rotated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere. 1.5 Br 1.5 Spin-coating was performed on a FAI+MAI substrate for 30 seconds, followed by oxidation in a drying oven for 3 hours to prepare a hole transport layer with a thickness of approximately 150 nm.
[0052] ITO / SnO2 / CsPbI 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD substrate;
[0053] Step 6: Under nitrogen atmosphere, a molybdenum oxide anode buffer layer is thermally evaporated and deposited on the Spiro-OMeTAD hole transport layer to obtain a layer with a thickness of 9 nm and an area of 2 cm². 2 The molybdenum oxide anolyte buffer layer, i.e., ITO / SnO2 / CsPbI, is obtained. 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD / Molybdenum oxide substrate;
[0054] Step 7: At room temperature, a metallic silver electrode is deposited on the molybdenum oxide anode buffer layer by thermal evaporation, resulting in a electrode with a thickness of 80 nm and an area of 0.04 cm². 2 The metallic silver electrode is used to complete the fabrication of perovskite solar cells.
[0055] The perovskite solar cells described above were tested, and their IV characteristic curves are shown below. Figure 2 As shown, the parameters are as follows:
[0056] condition PEC (%) <![CDATA[Jsc(mA / cm 2 )]]> <![CDATA[V oc (V)]]> FF (%) Control 8.18% 10.857 1.221 61.71% FAI+MAI 13.11% 15.032 1.256 69.29%
[0057] Example 2
[0058] A method for preparing high-efficiency inorganic perovskite solar cells by surface passivation includes:
[0059] Step 1: Clean the ITO / glass substrate 1 sequentially with conductive glass cleaning solution, deionized water, acetone and isopropanol for 20 minutes each, and set aside for later use. The sheet resistance of the ITO layer is 15 ohms. After cleaning, place it in UV-Ozone for 30 minutes. The thickness of the glass substrate with the ITO electrode cathode is 1 mm, and the thickness of the ITO electrode cathode is 100 nm.
[0060] Step 2: Place the glass substrate with ITO electrode anode and SnO2 spin-coated on it on a heating stage and anneal it at 150°C in air for 30 min to prepare a SnO2 electron transport layer with a thickness of 60 nm and obtain an ITO / SnO2 substrate.
[0061] Step 3: Dissolve 367 mg of PbBr2, 260 mg of CsI, and 138.4 mg of DMAI in 1.15 mL of DMSO, and stir at 100 °C until completely dissolved to obtain CsPbI. 1.5 Br 1.5 Solution; The ITO / SnO2 substrate was placed in a glove box under N2 environment, and 45 μL of 1M CsPbI solution was added. 1.5 Br 1.5 The solution was spin-coated onto the ITO / SnO2 substrate at 1000 rpm for 5 s and 2500 rpm for 50 s, and then allowed to stand for 30 min. The CsPbI solution was then spin-coated onto the substrate. 1.5 Br 1.5 The solution-containing ITO / SnO2 substrate was annealed on a hot plate at 170℃ for 10 min to prepare CsPbI with a thickness of 200-600 nm. 1.5 Br 1.5 The thin film, namely the ITO / SnO2 / CsPbI film, is obtained. 1.5 Br 1.5 Base;
[0062] Step 4: Dissolve 8 mg of FAI and 0.5 mg of MAI solid in 1 mL of isopropanol, and stir at room temperature until completely dissolved to obtain a mixed solution of FAI + MAI; Add ITO / SnO2 / CsPbI 1.5 Br 1.5 The substrate was placed in a nitrogen atmosphere in a glove box, and 30 μL of the mixed solution was incubated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere. 1.5 Br 1.5 Spin-coating was performed on the substrate for 30 seconds; the ITO / SnO2 / CsPbI solution was then spin-coated. 1.5 Br 1.5 The substrate was annealed on a hot plate at 100℃ for 10 min to prepare a 60 nm thick FAI+MAI passivation layer, thus obtaining ITO / SnO2 / CsPbI.1.5 Br 1.5 / FAI+MAI substrate;
[0063] Step 5: Dissolve 72.3 mg of Spiro-OMeTAD in 1 mL of chlorobenzene and stir at room temperature until completely dissolved to obtain a Spiro-OMeTAD solution; Add ITO / SnO2 / CsPbI 1.5 Br 1.5 The FAI+MAI substrate was placed in a glove box under a nitrogen atmosphere, and 30 μL of Spiro-OMeTAD was rotated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere. 1.5 Br 1.5 Spin-coating was performed on a FAI+MAI substrate for 30 seconds, followed by oxidation in a drying oven for 3 hours to prepare a hole transport layer with a thickness of approximately 150 nm.
[0064] ITO / SnO2 / CsPbI 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD substrate;
[0065] Step 6: Under nitrogen atmosphere, a molybdenum oxide anode buffer layer is thermally evaporated and deposited on the Spiro-OMeTAD hole transport layer to obtain a layer with a thickness of 11 nm and an area of 2 cm². 2 The molybdenum oxide anolyte buffer layer, i.e., ITO / SnO2 / CsPbI, is obtained. 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD / Molybdenum oxide substrate;
[0066] Step 7: At room temperature, a metallic silver electrode is deposited on the molybdenum oxide anode buffer layer by thermal evaporation, resulting in a electrode with a thickness of 80 nm and an area of 0.04 cm². 2 The metallic silver electrode is used to complete the fabrication of perovskite solar cells.
[0067] Example 3
[0068] A method for preparing high-efficiency inorganic perovskite solar cells by surface passivation includes:
[0069] Step 1: Clean the ITO / glass substrate 1 sequentially with conductive glass cleaning solution, deionized water, acetone and isopropanol for 20 minutes each, and set aside for later use. The sheet resistance of the ITO layer is 12 ohms. After cleaning, place it in UV-Ozone for 20 minutes. The thickness of the glass substrate with the ITO electrode cathode is 0.8 mm, and the thickness of the ITO electrode cathode is 80 nm.
[0070] Step 2: Place the glass substrate with ITO electrode anode and SnO2 spin-coated on it on a heating stage and anneal it at 150°C in air for 30 min to prepare a SnO2 electron transport layer with a thickness of 40 nm and obtain an ITO / SnO2 substrate.
[0071] Step 3: Dissolve 367 mg of PbBr2, 260 mg of CsI, and 138.4 mg of DMAI in 1.15 mL of DMSO, and stir at 100 °C until completely dissolved to obtain CsPbI. 1.5 Br 1.5 Solution; The ITO / SnO2 substrate was placed in a glove box under N2 environment, and 42 μL of 1M CsPbI solution was added. 1.5 Br 1.5 The solution was spin-coated onto the ITO / SnO2 substrate at 1000 rpm for 5 s and 2500 rpm for 50 s, and then allowed to stand for 25 min. The CsPbI solution was then spin-coated onto the substrate. 1.5 Br 1.5 The solution-containing ITO / SnO2 substrate was annealed on a hot plate at 170℃ for 9 min to prepare a CsPbI layer with a thickness of 400 nm. 1.5 Br 1.5 The thin film, namely the ITO / SnO2 / CsPbI film, is obtained. 1.5 Br 1.5 Base;
[0072] Step 4: Dissolve 8 mg of FAI and 0.5 mg of MAI solid in 1 mL of isopropanol, and stir at room temperature until completely dissolved to obtain a mixed solution of FAI + MAI; Add ITO / SnO2 / CsPbI 1.5 Br 1.5 The substrate was placed in a nitrogen atmosphere in a glove box, and 30 μL of the mixed solution was incubated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere. 1.5 Br 1.5 Spin-coating was performed on the substrate for 30 seconds; the ITO / SnO2 / CsPbI solution was then spin-coated. 1.5 Br 1.5 The substrate was annealed on a hot plate at 100℃ for 9 min to prepare a 50 nm thick FAI+MAI passivation layer, thus obtaining ITO / SnO2 / CsPbI. 1.5 Br 1.5 / FAI+MAI substrate;
[0073] Step 5: Dissolve 72.3 mg of Spiro-OMeTAD in 1 mL of chlorobenzene and stir at room temperature until completely dissolved to obtain a Spiro-OMeTAD solution; Add ITO / SnO2 / CsPbI 1.5 Br1.5 The FAI+MAI substrate was placed in a glove box under a nitrogen atmosphere, and 30 μL of Spiro-OMeTAD was rotated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere. 1.5 Br 1.5 Spin-coating was performed on a FAI+MAI substrate for 30 seconds, followed by oxidation in a drying oven for 3 hours to prepare a hole transport layer with a thickness of approximately 150 nm.
[0074] ITO / SnO2 / CsPbI 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD substrate;
[0075] Step 6: Under nitrogen atmosphere, a molybdenum oxide anode buffer layer is thermally evaporated and deposited on the Spiro-OMeTAD hole transport layer to obtain a layer with a thickness of 10 nm and an area of 2 cm². 2 The molybdenum oxide anolyte buffer layer, i.e., ITO / SnO2 / CsPbI, is obtained. 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD / Molybdenum oxide substrate;
[0076] Step 7: At room temperature, a metallic silver electrode is deposited on the molybdenum oxide anode buffer layer by thermal evaporation, resulting in a electrode with a thickness of 80 nm and an area of 0.04 cm². 2 The metallic silver electrode is used to complete the fabrication of perovskite solar cells.
[0077] It is understood that the above detailed description of the present invention is for illustrative purposes only and is not intended to limit the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention to achieve the same technical effects; as long as the usage requirements are met, they are all within the protection scope of the present invention.
Claims
1. A method for preparing high-efficiency inorganic perovskite solar cells by surface passivation, characterized in that, include Step 1: Select a glass substrate with an ITO electrode cathode; Step 2: Prepare a SnO2 electron transport layer on the surface of the ITO electrode anode to obtain an ITO / SnO2 substrate; Step 3: A mixed solution of DMAI, CsI, and PbBr2 is obtained in one step, and CsPbI is prepared on the SnO2 electron transport layer. 1.5 Br 1.5 Perovskite films were obtained, yielding ITO / SnO2 / CsPbI 1.5 Br 1.5 Base; Step 4, in CsPbI 1.5 Br 1.5 Spin-coating a mixed solution of FAI and MAI onto a perovskite thin film to prepare a FAI+MAI passivation layer, yielding an ITO / SnO2 / CsPbI layer. 1.5 Br 1.5 / FAI+MAI substrate; Step 5: Spin-coating Spiro-OMeTAD solution onto the surface of the FAI+MAI passivation layer to prepare a hole transport layer, resulting in ITO / SnO2 / CsPbI 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD substrate; Step 6: Deposit an anolyte buffer layer—molybdenum oxide—on the surface of the hole transport layer to obtain ITO / SnO2 / CsPbI 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD / Molybdenum oxide substrate; Step 7: Deposit a metallic silver electrode on the anode buffer layer-molybdenum oxide to prepare an all-inorganic perovskite solar cell with surface passivation; The ITO / SnO2 / CsPbI in step 3 1.5 Br 1.5 The preparation of the substrate includes: Dissolve 367 mg of PbBr2, 260 mg of CsI, and 138.4 mg of DMAI in 1.15 mL of DMSO and stir at 100 °C until completely dissolved to obtain CsPbI. 1.5 Br 1.5 Solution; The ITO / SnO2 substrate was placed in a glove box under N2 environment, and 40-45 μL of 1M CsPbI was added. 1.5 Br 1.5 The solution was spin-coated onto the ITO / SnO2 substrate at rotation speeds of 1000 rpm for 5 s and 2500 rpm for 50 s. Spin-coated with CsPbI 1.5 Br 1.5 The solution-containing ITO / SnO2 substrate was annealed on a hot plate at 170℃ for 8-10 min to prepare CsPbI with a thickness of 200-600 nm. 1.5 Br 1.5 The thin film, namely the ITO / SnO2 / CsPbI film, is obtained. 1.5 Br 1.5 Base; The preparation of the FAI+MAI passivation layer in step 4 includes: Take 8 mg of FAI and 0.5 mg of MAI solid and dissolve them in 1 mL of isopropanol. Stir at room temperature until completely dissolved to obtain a mixed solution of FAI and MAI. Will ITO / SnO2 / CsPbI 1.5 Br 1.5 The substrate was placed in a nitrogen atmosphere in a glove box, and 30 μL of the mixed solution was incubated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere. 1.5 Br 1.5 Spin-coat the substrate for 30 seconds; Spin-coating ITO / SnO2 / CsPbI with a mixed solution 1.5 Br 1.5 The substrate was annealed on a hot plate at 100℃ for 8-10 min to prepare a FAI+MAI passivation layer with a thickness of 10-60 nm, thus obtaining ITO / SnO2 / CsPbI 1.5 Br 1.5 / FAI+MAI substrate.
2. The method for preparing high-efficiency inorganic perovskite solar cells by surface passivation according to claim 1, characterized in that, The thickness of the glass substrate with the ITO electrode cathode in step 1 is 0.7-1 mm, and the thickness of the ITO electrode cathode is 50-100 nm.
3. The method for preparing high-efficiency inorganic perovskite solar cells by surface passivation according to claim 1, characterized in that, Before use, the glass substrate with the ITO electrode cathode in step 1 is ultrasonically cleaned in conductive glass cleaning solution, deionized water, acetone and isopropanol for 20 minutes in sequence.
4. The method for preparing high-efficiency inorganic perovskite solar cells by surface passivation according to claim 3, characterized in that, After cleaning, the glass substrate with the ITO electrode cathode is treated in a UV-Ozone for 15-30 minutes.
5. The method for preparing high-efficiency inorganic perovskite solar cells by surface passivation according to claim 1, characterized in that, The electron transport layer fabrication of the ITO / SnO2 substrate in step 2 includes: 50 μL of SnO2 solution was spin-coated in air at 4000 rpm for 30 s onto a glass substrate with an ITO electrode anode that had been treated with UV-Ozone. A glass substrate with an ITO electrode anode and SnO2 spin-coated was placed on a heating stage and annealed at 150°C in air for 30 min to prepare a SnO2 electron transport layer with a thickness of 10 nm to 60 nm, thus obtaining an ITO / SnO2 substrate.
6. The method for preparing high-efficiency inorganic perovskite solar cells by surface passivation according to claim 1, characterized in that, The preparation of the hole transport layer in step 5 includes: Dissolve 72.3 mg of Spiro-OMeTAD in 1 mL of chlorobenzene and stir at room temperature until completely dissolved to obtain a Spiro-OMeTAD solution. Will ITO / SnO2 / CsPbI 1.5 Br 1.5 The FAI+MAI substrate was placed in a glove box under a nitrogen atmosphere, and 30 μL Spiro-OMeTAD was rotated at 3000 rpm in an ITO / SnO2 / CsPbI2 atmosphere. 1.5 Br 1.5 A hole transport layer was prepared by spin-coating on a FAI+MAI substrate for 30 seconds, resulting in ITO / SnO2 / CsPbI. 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD substrate.
7. The method for preparing high-efficiency inorganic perovskite solar cells by surface passivation according to claim 1, characterized in that, The preparation of the anode buffer layer in step 6 includes: Under nitrogen atmosphere, a molybdenum oxide anolyte buffer layer was deposited on the Spiro-OMeTAD hole transport layer using thermal evaporation to obtain a layer with a thickness of 9-11 nm and an area of 2 cm². 2 The molybdenum oxide anolyte buffer layer, i.e., ITO / SnO2 / CsPbI, is obtained. 1.5 Br 1.5 / FAI+MAI / Spiro-OMeTAD / Molybdenum oxide substrate.
8. The method for preparing high-efficiency inorganic perovskite solar cells by surface passivation according to claim 1, characterized in that, The preparation of the silver electrode in step 7 includes: At room temperature, a metallic silver electrode was deposited on a molybdenum oxide anode buffer layer using thermal evaporation, resulting in a electrode with a thickness of 80 nm and an area of 0.04 cm². 2 The metallic silver electrode is used to complete the fabrication of perovskite solar cells.
Citation Information
Patent Citations
Method for improving environmental stability of inorganic CsPbI3 perovskite thin film
CN115020598A
